2009
DOI: 10.1128/jcm.01668-08
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Oligonucleotide Array for Direct Detection of Fungi in Sputum Samples from Patients with Cystic Fibrosis

Abstract: Cystic fibrosis (CF) is the most common inherited genetic disease in Caucasian populations. Besides bacteria, many species of fungi may colonize the respiratory tract of these patients, sometimes leading to true respiratory infections. In this study, an oligonucleotide array capable of identifying 20 fungal species was developed to directly detect fungi in the sputum samples of CF patients. Species-specific oligonucleotide probes were designed from the internal transcribed spacer (ITS) regions of the rRNA oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
2
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 42 publications
2
60
2
1
Order By: Relevance
“…Other centers have reported that S. apiospermum and A. terreus are the second and third most frequently observed filamentous fungi (42). However, the routine media and incubation time used in our study are not optimal for species like S. apiospermum and E. dermatitidis, and thus, the prevalence rates of these are probably underestimated (9,38).…”
Section: Discussioncontrasting
confidence: 39%
“…Other centers have reported that S. apiospermum and A. terreus are the second and third most frequently observed filamentous fungi (42). However, the routine media and incubation time used in our study are not optimal for species like S. apiospermum and E. dermatitidis, and thus, the prevalence rates of these are probably underestimated (9,38).…”
Section: Discussioncontrasting
confidence: 39%
“…The full complexity of the microbial community in the CF lung and the interactions among its members are only beginning to be appreciated (8,25,63). Systematic studies are needed to understand how iron availability-impacted by both host cells and the microbiome-affects this ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…As for mycological examination, it requires skill and expertise and may lead to false-negative results for polymicrobial specimens like sputum samples because of the more rapid and more extensive growth of other molds frequently associated with this fungus, like Aspergillus fumigatus (19). Several molecular methods have been proposed for detection of the fungus from sputum samples (20)(21)(22)(23)(24), but as culture methods, they do not allow the differentiation between airway colonization and sensitization of the patient or respiratory infection in the CF context, which has important implications for patient management.…”
mentioning
confidence: 99%